Evaluation of Nutrition Knowledge and Dietary Practices of Pregnant and Lactating Adolescents in Turkana South Sub-county - NAMUYA, Benjamin; Serrem, Charlotte; Kamau, Heka (African Journal of Nutrition and Dietetics, 2025)
Pregnant and lactating adolescents have increased nutritional needs due to physiological changes and fetal or neonatal demands. Despite the dietary implications of pregnancy among adolescents, most of them often do not meet their daily requirements due to various factors, especially among marginalized communities such as the Turkana community. Despite these challenges, limited studies have examined the factors influencing dietary practices in marginalized populations such as Turkana County. The current study, therefore, assessed the nutrition knowledge, dietary practices, and factors affecting pregnant and lactating adolescents in Turkana South sub-county. The study adopted a cross-sectional design and multistage sampling technique to select 384 pregnant and lactating adolescents. Data were collected using questionnaires evaluating mothers’ nutrition knowledge about breastfeeding practices, complementary feeding, consistency of meals, dietary diversity, and feeding practices, and analysed using GenStat version 18.0. The results indicated that most respondents were unemployed (62.3%), and their households were in the poorest quintile (71.5%), negatively affecting their dietary diversity. It was also noted that most of the respondents had no formal education (44.4%) and had low nutrition knowledge (67.3%), which directly affected their dietary diversity (p < 0.05). Most respondents did not meet their daily caloric intake (725.06 and 805.29 kcal for pregnant and lactating women, respectively) and other vital minerals, including calcium and iron, vital during pregnancy and lactation. Improving general and nutrition-specific education among adolescent mothers may enhance dietary practices, supporting maternal and infant health.